A viologen-functionalized metal–organic framework for efficient CO2 photoreduction reaction. Issue 54 (14th June 2022) - Wang, Tong; Zhang, Lei; Liu, Jiang; Li, Xiao-Xin; Yuan, Lin; Li, Shun-Li; Lan, Ya-Qian
Abstract : A viologen-functionalized metal–organic framework (MIL-125-RV 2+ ) achieved CO2 reduction under visible light, which provided a strategy for the construction of novel CO2 RR photocatalysts by combining color-tunable organics with framework materials. Abstract : Here, a viologen-functionalized metal–organic framework (MOF), MIL-125-RV 2+, was obtained by modification of MIL-125-NH2 with viologen molecules. MIL-125-RV 2+, the first viologen-based MOF for photocatalytic CO2 RR, exhibited excellent photocatalytic activity and high selectivity for HCOO − . The strategy of using photo-responsive color-changing organics to functionalize the MOF is significant for achieving efficient CO2 RR.